2017
DOI: 10.1080/15332640.2017.1317310
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in treatment outcomes among adults with stimulant use disorders after a dosed exercise intervention

Abstract: The current study examined differences in substance abuse treatment outcomes among racial and ethnic groups enrolled in the Stimulant Reduction Intervention using Dosed Exercise (STRIDE) trial, a multisite randomized clinical trial implemented through the National Institute on Drug Abuse’s (NIDA’s) Clinical Trials Network (CTN). STRIDE aimed to test vigorous exercise as a novel approach to the treatment of stimulant abuse compared to a health education intervention. A hurdle model with a complier average causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Moreover, persons with addiction also diagnosed with mental health conditions (e.g., depression) are less likely to fully engage with treatment and are more likely to relapse (Weinstock et al, 2007). Because exercise can improve mental health (Chekroud et al, 2018) and is related to reduced rates of relapse in those overcoming addictions (Linke et al, 2019;Linke & Ussher, 2015;Park et al, 2016;Sanchez et al, 2017), understanding factors related to increases in exercise behaviors among people seeking recovery could be helpful in assisting their long-term recovery.…”
mentioning
confidence: 99%
“…Moreover, persons with addiction also diagnosed with mental health conditions (e.g., depression) are less likely to fully engage with treatment and are more likely to relapse (Weinstock et al, 2007). Because exercise can improve mental health (Chekroud et al, 2018) and is related to reduced rates of relapse in those overcoming addictions (Linke et al, 2019;Linke & Ussher, 2015;Park et al, 2016;Sanchez et al, 2017), understanding factors related to increases in exercise behaviors among people seeking recovery could be helpful in assisting their long-term recovery.…”
mentioning
confidence: 99%
“…First, interventions utilized in this model have been developed for White populations and more culturally appropriate interventions among YBMSM are needed. [26][27][28][29] We use a model that was developed for a YBMSM population, and future iterations of this work will consider the development and deployment of such interventions. Better contextual data on the association between stimulant use and engagement in the HIV prevention and treatment continua will be helpful in adapting these interventions for YBMSM.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges of addressing the stimulant epidemic among YBMSM is the development of culturally appropriate interventions for stimulant use treatment in this population, increasingly identified as a gap in the scientific literature and current public health policies in addressing psychosocial and structural barriers faced by Black populations. [26][27][28][29] This study extends an existing agent-based network model (ABNM), 30 parameterized largely with data collected in Illinois, to address the impact of stimulant use on the ART and PrEP continua and downstream HIV incidence among YBMSM. Interventions that are designed to treat stimulant use dependency (such as residential rehabilitation and medication-assisted treatment for methamphetamine use through mirtazapine) are thus likely to improve engagement in the HIV treatment and continua and are simulated to project their impact on HIV incidence and inform next steps in the GTZ planning efforts in Illinois.…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistent pattern was also found for other drugs. Two studies found Black participants entered treatment with lower rates of stimulant (Sanchez, Chartier, et al, 2015;Sanchez et al, 2017) and methadone use (Wu, Blazer, Stitzer, Patkar, & Blaine, 2008), whereas others showed higher rates of current opioid use (Potter et al, 2013), other drug use (Cochran, Stitzer, Nunes, Hu, & Campbell, 2014), blunt use (Montgomery et al, 2019), and lifetime heroin use (E. S. Brown et al, 2010) relative to their White, and in some cases, Hispanic, counterparts. Further, one study using data from multiple CTN trials showed higher rates of combined opiate and stimulant use among Black compared to White adults (Brooks et al, 2013).…”
Section: Baseline Characteristicsmentioning
confidence: 99%